The Stock Market Liberalization and Enterprise Innovation Data Chinese Listed Firms Model: OLS (KASBIT Business Journal, 2023)
The Aim of this study is to find out the Stock Market Liberalization and enterprise innovation in China. In order to reach the results, the quantitative method is used in which the OLS technique is used specifically. Results of the study show that enterprise innovation can help to reduce financial imbalances and lends support to the concept of "using liberalization to push transformation" in enterprise innovation, which is a basic policy of Chinese financial reopening policy. Moreover, this research determined that governance structures are important, trying to imply that expediting the market-based method could be efficient in exacerbating the impact of Enterprise innovation and sustainable development. This study can be useful for Chinese enterprises and enterprises in the world, stock markets, and financial institutions.